Breast Imaging - Kuzmiak, Cherie M. (IntechOpen, 2018)
Early detection of breast cancer with screening mammography is still the best method we have in saving countless women's lives and decreasing the harms of overtreatment. This textbook encompasses relevant topics in daily patient care with breast imaging to technical innovations for improving breast cancer detection and treatment.